Non-Melanoma Skin Cancer: news from microbiota research. (3rd July 2020) - Squarzanti, Diletta Francesca; Zavattaro, Elisa; Pizzimenti, Stefania; Amoruso, Angela; Savoia, Paola; Azzimonti, Barbara
Abstract: Recently, research has been deeply focusing on the role of the microbiota in numerous diseases, either affecting the skin or other organs. What it is well established is that its dysregulation promotes several cutaneous disorders (i.e. psoriasis and atopic dermatitis). To date, little is known about its composition, mediators and role in the genesis, progression and response to therapy of Non-Melanoma Skin Cancer (NMSC). Starting from a bibliographic study, we classified the selected articles into four sections: i) normal skin microbiota; ii) in vitro study models; iii) microbiota and NMSC and iv) probiotics, antibiotics and NMSC. What has emerged is how skin microflora changes, mainly represented by increases of Staphylococcus aureus, Streptococcus pyogenes and Pseudomonas aeruginosa strains, modifications in the mutual quantity of β-Human papillomavirus genotypes, of Epstein Barr Virus and Malassezia or candidiasis, may contribute to the induction of a state of chronic self-maintaining inflammation, leading to cancer. In this context, the role of S. aureus and that of specific antimicrobial peptides look to be prominent. Moreover, although antibiotics may contribute to carcinogenesis, due to their ability to influence the microbiota balance, specific probiotics, such as Lacticaseibacillus rhamnosus GG, Lactobacillus johnsonii NCC 533 and Bifidobacteria spp., may be protective.